Diagnóstico do consumo de alimentos orgânicos no município de Pau dos Ferros-RN - Silva, Francimagne Ribeiro da (Universidade Federal Rural do Semi-Árido, 2019)
The use of chemical substances has predominated in agricultural production systems. And Brazil has the highest amount of pesticides used in the world. In view of this, part of the population has constantly demanded for healthier foods, in search of a better quality of life. In 2014, the highest incidence of notification of poisoning by pesticides in Brazil was recorded in the SINAN Notification Disease Information System, and between 2007 and 2015, 84,206 cases were reported. An alternative to these problems would be the adoption of Organic Production Systems. Therefore, a diagnosis of organic food consumption was carried out in the city of Pau dos Ferros / RN, followed by the profile of the consumers and the factors that most influence the purchases. The studies were conducted through "on-site" visits, through the application of questionnaires to consumers, supermarkets, rural areas, the city's free trade show, semi-structured interview, and photographic records. From the data obtained, it can be verified that the population interviewed has little or no knowledge about organic foods, their production and their health and environmental benefits. There is the consumption of these foods only by a part of the population, to which they do not know the real reasons for being organic. The research showed that the lack of information and the lack of supply for these products are the main causes of organic consumption being reduced in Pau dos Ferros. So as there is little supply, there is little demand. Maybe if there were more advertising or ads on these foods, demand in Pau dos Ferros would increase.
Keywords: Alimentos saudáveis consumo saúde; Healthy food consumption cheers; ENGENHARIAS::ENGENHARIA SANITARIA